PERUBAHAN BENTUK PADA PELAMINAN ACEH DI KOTA LHOKSEUMAWE DITINJAU DARI ESTETIKA ISLAM - Nur Anissa Anissa (Ranah Seni, 2021)
Knowing the Changes in the Form of the Aceh Aisle in the City of Lhokseumawe in terms of Islamic aesthetics. The research method used is descriptive method, in which the researcher describes several Acehnese avenues in the city of Lhokseumawe. The population that I use is 10 types of aisle, with 5 samples being my research. Researchers used data collection techniques and instruments, namely by observation, interviews, and documentation. The purpose of this study is to determine the changes in the shape of the Aceh aisle which is increasingly developing with the times, as well as to broaden people's insights about the changes that have occurred in the Aceh aisle. Thus, it can be interpreted that the techniques and tools that researchers use can assist researchers in capturing research data. The results of this study explain that. Changes in the aesthetic elements of the Aceh aisle in the city of Lhokseumawe, from the hulubalang era to modern have changes in positive terms, and have changes in negative terms, in terms of colors and the interior used in the Aceh aisle. The colors and interiors applied in modern times leave characteristics that should be preserved in the traditional Acehnese aisle. In the Aceh aisle, there are values ​​of the beauty of Islamic art that can be expressed in Islamic aesthetics, the presence of artwork in the aisle that uses geometric shapes, is a style of Islamic art.